2021
DOI: 10.1007/s10461-021-03337-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Impact of COVID-19 on Pre-Exposure Prophylaxis (PrEP) Care

Abstract: COVID-19 is a public health crisis that has fundamentally altered health care provision. The purpose of this study was to examine the impact of COVID-19 on pre-exposure prophylaxis (PrEP) care. We reviewed all patient records for those who presented for PrEP care at a PrEP program in Providence, Rhode Island from September 1st, 2019 to May 29th, 2020. The number of PrEP encounters decreased but was not significantly different over time (ps > .05). Patients were still able to access PrEP clinical services durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 9 publications
0
24
1
Order By: Relevance
“…Third, this analysis includes the time period after the start of the COVID-19 pandemic. Many clinics have identified drop-offs in PrEP clinic visits during the initial COVID-19 pandemic [ 32 ] though some have observed increases in PrEP visits [ 33 ]. Anecdotally, the clinic continued to see PrEP patients with minimal disruption during the COVID-19 pandemic; thus, we do not believe this had a major bearing on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this analysis includes the time period after the start of the COVID-19 pandemic. Many clinics have identified drop-offs in PrEP clinic visits during the initial COVID-19 pandemic [ 32 ] though some have observed increases in PrEP visits [ 33 ]. Anecdotally, the clinic continued to see PrEP patients with minimal disruption during the COVID-19 pandemic; thus, we do not believe this had a major bearing on our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of the pandemic has varied greatly depending on the setting and geographic location. [49][50][51] In addition, racial and socioeconomic disparities in both COVID-19 and HIV testing, infection, and outcomes have been documented. [52][53][54] Demographic characteristics were self-reported and, in the case of race and ethnicity, could be left blank, limiting our ability to observe whether individuals of Hispanic decent were adequately provided PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior experiences with the HIV epidemic were instrumental in responding and ensuring communities continue to access HIV prevention services [ 18 , 19 ]. Numerous studies reported substantially reduced access and utilization of pre-exposure prophylaxis (PrEP), initial PrEP intake visits, and increases in refill lapses during the COVID-19 pandemic [ 20 , 21 ]. Many US cities also reported significant decreases in HIV testing rates – San Francisco, for example, reporting a 40% decrease citywide and a 90% decrease in community-based testing [ 20 ].…”
Section: Introductionmentioning
confidence: 99%